The Role of Technology in Promoting Student Engagement in Islamic Religious Education - syifaayulia; Yusnaini (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The significance of technology in enhancing student participation in Islamic Religious Education (PAI) is important in the contemporary digital age.  The rapid progression of information and communication technology (ICT) has revolutionized numerous facets of education, including PAI.  This study seeks to examine the influence of technology on enhancing student interest and engagement in PAI learning, as well as to comprehend how technological tools captivate and sustain students' attention.  A qualitative descriptive research design utilizing content analysis was employed to collect data from various scientific databases, including Google Scholar, ResearchGate, ScienceDirect, ERIC, DOAJ, Portal Garuda, and SINTA, to assure credibility and timeliness.  The findings indicate that technology in PAI transcends its position as a teaching aid, acting instead as a catalyst for pedagogical reform that fosters comprehensive student participation.  When utilized correctly and proportionately, technology fosters an engaging, contextual, and significant learning environment that facilitates the deeper and more practical integration of Islamic ideals into students' lives.  Technology plays a crucial role in changing PAI training into a more engaging, significant, and character-enhancing experience.  When utilized judiciously and combined with effective educational strategies, technology acts as a crucial catalyst for improving student engagement and fostering Islamic values in a more relevant and significant way.